Community Structure of Benthic Epifauna in Mangrove Forest Rehabilitation of Kedaburapat Village Kepulauan Meranti District - Syafrhani, Wan Nabila; Efriyeldi, Efriyeldi; Zulkifli, Zulkifli (Journal of Coastal and Ocean Sciences, 2021)
The mangrove forest area is important for benthic epifauna because it is a habitat for benthic epifauna. This research was conducted in September 2020 in the mangrove forest rehabilitation area of ​​Kedaburapat Village, Kepulauan Meranti. In this study, it was divided into 2 areas, namely the mangrove planting period 2018 and the planting period 2019. The result of this study found 18 species from 2 classes, Gastropods and Malacostraca. Gastropod class namely Littoraria melanostoma, Nerita balteata and Sphaerassiminea miniata; and Malacostraca classes namely Macrophthalmus convexus, Clibanarius longitarsus and Clibanarius ambonensis. Macrozoobenthic abundance values ​​ranged from 50.33 to 46.63 ind/m2, the diversity index value (H ') was between 1.23-2.27, the dominance index value was 0.30-0.65, the uniformity index (E) ranged from 0.32-0.67 and the distribution ranges from 0.94-1.61. Water quality parameters measured include temperature, salinity, pH, organic matter, TSS and substrates that affect the presence of benthic epifauna.